The effect of body mass index on neonatal outcomes in Chinese women with polycystic ovary syndrome - Guo, Haiyan; Wang, Bian; Gao, Hongyuan; Zhu, Qianqian (Frontiers in Medicine, 2022)
Aim This study aimed to explore the effect of body mass index (BMI) on neonatal outcomes in patients with polycystic ovary syndrome following the frozen embryo transfer (FET). Methods This study included 1,676 singletons born from mothers with polycystic ovary syndrome (PCOS) after FET between 1 Jan 2007 and 31 Dec 2019. BMI was categorized into three groups: underweight (BMI less than 18.5 kg/m2), normal weight (BMI between 18.5 and 24.9 kg/m2), and overweight (BMI between 25.0 and 29.9 kg/m2). Logistic regression models with generalized estimating equations were used for clustering by patients to explore the effect of BMI on neonatal outcomes. Results When compared to normal-weight mothers, the rate of large for gestational age (LGA) babies (adjusted odds ratio [aOR] 0.45, 95% confidence interval [95%CI] 0.22–0.93) significantly decreased for underweight mothers and significantly increased (aOR 1.82, 95%CI 1.38–2.41) for overweight mothers. The rate of high birth weight among infants from overweight mothers (aOR 1.75, 95%CI 1.15–2.65) was significantly higher than those from normal-weight mothers after adjusting for known confounding factors. The rate of small for gestational age (SGA) singleton (aOR 2.37, 95%CI 1.14–4.93) was lower among underweight mothers than normal-weight mothers. Conclusion Maternal underweight was a significant protective factor against LGA infants for singletons born from patients with PCOS after FET, whereas maternal overweight was an adverse factor for LGA infants.